2022
DOI: 10.3389/fmed.2022.851644
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Macular Edema Detection Using End-to-End Deep Fusion Model and Anatomical Landmark Visualization on an Edge Computing Device

Abstract: PurposeDiabetic macular edema (DME) is a common cause of vision impairment and blindness in patients with diabetes. However, vision loss can be prevented by regular eye examinations during primary care. This study aimed to design an artificial intelligence (AI) system to facilitate ophthalmology referrals by physicians.MethodsWe developed an end-to-end deep fusion model for DME classification and hard exudate (HE) detection. Based on the architecture of fusion model, we also applied a dual model which included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The deep fusion model was evaluated using an edge device with limited computer resources that could be mounted on a portable device and used easily by the patient for an eye examination at an appropriate time. 27 Besides, that study reported a good performance in classifying DME through the deep fusion model, with the model reporting a sensitivity of 96% and a specificity of 90%. 27 …”
Section: Ai-based Medical Images Analysis In Dmmentioning
confidence: 83%
See 1 more Smart Citation
“…The deep fusion model was evaluated using an edge device with limited computer resources that could be mounted on a portable device and used easily by the patient for an eye examination at an appropriate time. 27 Besides, that study reported a good performance in classifying DME through the deep fusion model, with the model reporting a sensitivity of 96% and a specificity of 90%. 27 …”
Section: Ai-based Medical Images Analysis In Dmmentioning
confidence: 83%
“…As the number of studies related to medical images based on deep learning, including a convolution neural network (CNN), has increased significantly, many CNN-based medical imaging studies using fundoscopy or optical coherence tomography (OCT) have been reported since 2019 ( Table 1 ). 18 19 20 21 22 23 24 25 26 27 28 29 30 This was followed by diabetic foot (7.9%, 18/227 cases) and diabetic neuropathy (2.7%, 6/227 cases) ( Fig. 3A ).…”
Section: Ai-based Medical Images Analysis In Dmmentioning
confidence: 96%
“…AI algorithms designed for the automated detection of exudates and macula in DME contribute to streamlining the diagnostic process. Furthermore, this automated detection aids in grading the severity of the condition, providing valuable insights for clinicians managing DME cases [ 26 ]. Predicting treatment responses in patients with DME, particularly in the context of anti-VEGF therapy, has been a focus of exploration for AI techniques.…”
Section: Reviewmentioning
confidence: 99%
“…The proposal of an end-to-end deep fusion model represents a cutting-edge approach to DME detection. Leveraging anatomical landmarks and operating on edge computing devices, this model aims to enhance the accuracy and efficiency of DME detection [ 26 ]. This holistic approach combines various deep-learning techniques for a more comprehensive assessment (Table 1 ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation